FREQUENCY OF DENTOFACIAL ASYMMETRIES: A CROSS-SECTIONAL STUDY ON ORTHODONTIC PATIENTS - Bhateja, Nita Kumari; Fida, Mubassar; Shaikh, Attiya (Journal of Ayub Medical College Abbottabad, 2014)
Background: Correction of orthodontic asymmetries is crucial to achieve functional occlusion, aesthetics and stability of post orthodontic treatment results. To date valid frequency data of dentofacial asymmetries in Pakistani orthodontic patients do not exist to document orthodontic treatment need. The objectives of this study were to determine frequency of dento-facial asymmetries, severity of dental asymmetries and to determine difference in frequency of dentofacial asymmetries in mixed and permanent dentition. Methods: The sample of this cross-sectional study comprised of 280 patients (177 females and 103 males) with no history of previous orthodontic treatment having no craniofacial anomalies. Dento-facial asymmetries were assessed from pre-treatment records of patients. Descriptive statistics were used to determine frequency of dentofacial asymmetries and severity of dental asymmetries. Chi-square test was used to determine difference in frequency of dentofacial asymmetries in mixed and permanent dentition. Results: Seventy eight percent (219) of patients had noncoincident midlines, 67.5% (189) had mandibular midline asymmetry, 43.2% (122) had molar asymmetry, 15.7% (44) had mandibular arch asymmetry, 14.3% (40) had maxillary midline asymmetry, 13.6% (38) had maxillary arch asymmetry, 6.1% (17) had nose deviation, and 12.1% (34) had facial asymmetry and chin deviation. In most patients dental midlines were deviated from one another and from facial midline by ¼ lower incisor widths, while molar asymmetry was found in most patients by ¼ cusp width. Mandibular arch asymmetry was more frequent in permanent than mixed dentition (p=0.054). Conclusions: Non-coincident dental midline is most commonly seen. Nose deviation is least commonly observed. Mandibular arch asymmetry is more frequent in permanent than mixed dentition Keywords: Dentofacial, asymmetry, orthodontic, frequency